The stabilisation of export earnings: Two years' experience in stabex - Klaus-Peter Treydte (Intereconomics, 1977)
The Convention of Lomé anticipates several basic elements of a possible new international economic order. This relates particularly to the export earnings stabilisation system “Stabex“ whose merits and deficiencies after the first two years of application are discussed in the following contribution.
Keywords: 330; Stabex